Pembuatan Konten Media Sosial Menggunakan Model SOSTAC untuk Promosi Digital UMKM Kota Cimahi - Ramdani; Wahyu Budi Priatna (Universitas Muhammadiyah Prof. DR. Hamka, 2026)
The low utilization of social media as a digital marketing medium remains one of the primary challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Cimahi City, particularly due to limited knowledge of digital content creation and the continued reliance on conventional marketing methods. This study aims to implement the SOSTAC model in developing social media content as a digital promotion strategy for MSMEs in Cimahi City to enhance product exposure and promotional reach. The study employed an applied research method using a qualitative descriptive approach through observation, documentation, and social media insight analysis on Instagram, TikTok, Facebook, and YouTube platforms. The findings indicate that the implementation of short-form video content strategies that are informative, visually appealing, and aligned with current social media trends significantly improved account performance. The Instagram account generated 109,798 views with a reach of 48,087 accounts, TikTok achieved 24 thousand post views, while YouTube recorded 23.2 thousand views with 46.1 watch hours. Furthermore, audience engagement increased through likes, comments, shares, and follower growth across all social media platforms. These findings demonstrate that the implementation of the SOSTAC model is effective in supporting a more structured, systematic, and sustainable digital promotion process for MSMEs in Cimahi City.